Combined Training Intervention Targeting Medical and Nursing Staff Reduces Ciprofloxacin Use and Events of Urinary Tract Infection - Johannes Forster; Petra Schulze; Claudia Burger; Manuel Krone; Ulrich Vogel; Güzin Surat (Advances in Urology)
Inappropriate diagnosis of urinary tract infections (UTI) contributes to antimicrobial overuse. A combined training intervention for medical and nursing staff mainly addressing the analytic process reduced UTI events (9.20 vs. 7.36 per 1000 PD, −20.0%, p = 0.003) and the utilization rate of ciprofloxacin (11.6 vs. 3.5, −69.6 p = 0.001) in a Bavarian University Hospital. Combined training intervention—as part of an antibiotic stewardship program—can be effective in avoiding unnecessary urinalysis and reducing antibiotic consumption.